Snapshots in surgery: incidentally discovered cryptorchidism. Issue 5 (15th September 2014) - Nicholson, Margaret F.; Sehgal, Rishabh; Cunningham, Robert; Martin, Sean; Winter, Desmond C.
Key Clinical Message An 18‐year‐old was presented with a large inflamed appendix (compressed by the instrument) and a spermatic cord with right undescended testicle (cryptorchidism). Patients who undergo orchiopexy after age 12 years, or no orchiopexy, are 2–6 times as likely to have testicular cancer as those who undergo prepubertal orchiopexy.